2023
DOI: 10.3390/educsci13020143
|View full text |Cite
|
Sign up to set email alerts
|

Developing Pre-Service Teachers’ Professionalism by Sharing and Receiving Experiences in the Kampus Mengajar Program

Abstract: The low quality of teachers in Indonesia indicates that its current professional development programs are yet to reach an ideal form. Therefore, this research aims to determine how the kampus mengajar (teaching campus) program can be used to improve the professionalism of pre-service teachers to bridge the gap between theory and practice. Open interview questions were used to collect data from eleven pre-service teachers, two supervisors, and two principals involved in the kampus mengajar program with 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…This result corroborates the findings of another study in the Philippines, where preservice teachers also developed collaborative skills as part of the important competencies required for them to be effective in the teaching profession (Gonzales & Dinagsao, 2020). Similarly, other scholars found that pre-service teachers, during their activities at their practicing schools, participated in other activities such as handling paperwork and setting examination questions, thereby leading to the acquisition of administrative skills (Suyatno et al, 2023). The Suyatno et al (2023) study also reinforced the need for pre-service teachers to work collaboratively with other colleagues in a way that advances their understanding and skills.…”
Section: Collaborative and Administrative Skillssupporting
confidence: 87%
See 1 more Smart Citation
“…This result corroborates the findings of another study in the Philippines, where preservice teachers also developed collaborative skills as part of the important competencies required for them to be effective in the teaching profession (Gonzales & Dinagsao, 2020). Similarly, other scholars found that pre-service teachers, during their activities at their practicing schools, participated in other activities such as handling paperwork and setting examination questions, thereby leading to the acquisition of administrative skills (Suyatno et al, 2023). The Suyatno et al (2023) study also reinforced the need for pre-service teachers to work collaboratively with other colleagues in a way that advances their understanding and skills.…”
Section: Collaborative and Administrative Skillssupporting
confidence: 87%
“…Similarly, other scholars found that pre-service teachers, during their activities at their practicing schools, participated in other activities such as handling paperwork and setting examination questions, thereby leading to the acquisition of administrative skills (Suyatno et al, 2023). The Suyatno et al (2023) study also reinforced the need for pre-service teachers to work collaboratively with other colleagues in a way that advances their understanding and skills.…”
Section: Collaborative and Administrative Skillsmentioning
confidence: 85%
“…"I prioritise my on-thejob training as a pre-service teacher over personal matters unless in an unexpected crisis." The following statements differ from the result of the study conducted by Suyatno et al (2023), in which they reported that preservice teachers have a problem with time management, specifically with the learning schedule of the university and their schedule for the assignment. The result of the study shows that despite the different tasks given to the preservice teachers, it is important to observe time management.…”
Section: Observing Time Managementcontrasting
confidence: 77%
“…Researchers pointed out that a long-standing problem for teacher education is the gap between theory-based knowledge and experience-based knowledge. However, strategies for bridging this gap have been discussed at length by many scholars of teacher education (Ginsberg, 2023;Suyatno et al, 2023). Teacher education models have long been influenced by the concept of "technical rationality", which was formulated at modern Western universities.…”
Section: Professional Competencies Of Beginning Teachers and The Chal...mentioning
confidence: 99%